Pathologic and Risk Analysis of the Lojuela Castle (Granada-Spain): Methodology and Preventive Conservation for Medieval Earthen Fortifications. - Gutiérrez Carrillo, María Lourdes; Bestué Cardiel, Isabel; Molero Melgarejo, Emilio; Marcos-Cobaleda, María (MDPI, 2020)
This study presents a methodology generated for the preventive conservation of defensive earthen architecture, applied to the case of the Lojuela Castle (Lecrin Valley, Granada, Spain). In the application of the designed protocol, a multidisciplinary analysis of its patrimonial characteristics and multidimensional evaluation was developed, applying the technique of qualitative consultation to a group of experts—the Delphi method. This methodology allowed us to relate the hazard factors and the vulnerability of the asset for each group of risks that a ect it. The support of the method in with geographic information systems (GIS) has favored the production of predictive cartography and risk analysis—including the territorial dimensions and spatial interactions of the asset with the physical environment. This has facilitated the obtention of micro-zoning maps of each of the risks examined. The risk mapping in micro-zoning and the knowledge of the structure’s vulnerability represents an important contribution to the future conservation and management of this heritage. They favor strategies that minimize the incidence of risks and allow the prioritization of the conservation actions with a minimum economic investment, creating an e cient maintenance program. This will facilitate the protection, conservation and valorization decisions by the administration and the competent bodies involved in the protection of these sites.
Keywords: Arquitectura medieval; Fortificaciones; Restauración y conservación; Risk factors; Preventive conservation; Medieval earthen defensive architecture; Pathologic analysis